The Effects of Soft Tissue Flossing on Hamstring Range of Motion and Lower Extremity Power - Zachary Maust; Debbie Bradney; Sean M Collins; Caroline Wesley; Thomas G Bowman (North American Sports Medicine Institute, 2021)
# Background Flossing includes wrapping a specialized latex band around a muscle group providing compression, partially occluding blood flow, followed by performing exercises. This is hypothesized to improve flexibility by dissipating myofascial adhesions; however, research is lacking. # Objective To determine the effect of the application of a floss band to the thigh on hamstring flexibility and lower extremity power. # Design Crossover Study # Setting Exercise Physiology Laboratory. # Participants Twenty-one recreationally active individuals (8 male, 13 female; age = 22.62±2.99 years; height = 171.52±9.08 cm; mass = 73.57±11.37 kg). # Methods Three counterbalanced interventions were studied during body weight squats, lunges, and hamstring curls (without resistance): floss, sham, and control. The floss treatment included wrapping the Rogue Wide Voodoo Floss Band™ from the proximal knee to the gluteal fold at a pressure of 140 to 200 mmHg. The sham treatment included wrapping the same band in the same location with less pressure (10 to 40 mmHg) while the control treatment did not include floss band application. Hip flexion range of motion, via the straight leg raise, and power (single-leg vertical jump) were compared from pre-test to post-test using a 3x2 repeated measures ANOVA. # Results There was a significant interaction between time and session for hamstring flexibility (F~(2,40)~=17.54, *p*<0.001, η^2^=0.47). Post hoc tests showed significant differences between pre- (86.14±8.06 degrees) and post-test (90.81±7.69 degrees) for the floss session (*p*<0.001, Mean Difference=4.67, CI~95~=3.35-5.98) and between pre- (87.67±7.51 degrees) and post-test (89.86±7.88 degrees) for the sham session (*p*=0.001, Mean Difference=2.19, CI~95~=0.98-3.40). There were no significant interactions for jump power (F~(2,40)~=1.82, *P*=0.18, η^2^=0.08, 1-β=0.36). # Conclusions Flossing treatment increased hamstring flexibility more than the sham session without affecting lower body power. Flossing could be beneficial when treatment or performance preparation goals are increased flexibility without decreased power. Future studies should continue to examine the clinical effectiveness of flossing on an injured population.